Behaviour of steel fibre reinforced concrete slabs - Pei, Jinsong. (2009)
The thesis examines the flexural performance of steel fibre reinforced (SFR) concrete. The entire response history of SFR concrete thin square slabs under central concentrated load is investigated analytically and experimentally.